Outcome of expandable endoprosthesis: A single centre retrospective review - Singh, Vivek Ajit; Kunasingh, Dinesh Earnest; Haseeb, Amber; Yasin, Nor Faissal (SAGE Publications (UK and US), 2019)
Purpose: Expandable endoprosthesis allows limb salvage in children with an option to leading a better life. However, the revision rate and implant-related complications impose as a limitation in the skeletal immature. This study investigates the functional outcomes and complications related to expandable endoprosthesis in our centre. Materials and Methods: Twenty surviving patients with expandable endoprosthesis from 2006 till 2015 were scored using Musculoskeletal Tumour Society (MSTS) outcomes instrument and reviewed retrospectively for range of motion of respected joints, limb length discrepancy, number of surgeries performed, complications and oncological outcomes. Patients with less than 2 years of follow-up were excluded from this study. Results: Forty-five percentage patients reached skeletal maturity with initial growing endoprosthesis and 25% of patients were revised to adult modular prosthesis. One hundred fifty-seven surgeries were performed over the 9-year period. The average MSTS score was 90.83%. The mortality rate was 10% within 5 years due to advanced disease. Infection and implant failure rate was 15% each. The event-free survival was 50% and overall survival rate was 90%. Conclusion: There is no single best option for reconstruction in skeletally immature. This study demonstrates a favourable functional and survival outcome of paediatric patients with expandable endoprosthesis. The excellent MSTS functional scores reflect that patients were satisfied and adjusted well to activities of daily living following surgery despite the complications. © The Author(s) 2019.